Wegener's granulomatosis - Ghosh, Liton Chandra; Wadud, Md Shaheen (Journal of Dhaka National Medical College & Hospital, 2016)
Granulomatosis with polyangitis is an uncommon disorder that causes inflammation of the blood vessels in nose, sinuses, throat, lungs and kidneys. Granulomatosis with polyangitis formerly called Wegener's granulomatosis. Wegener's granulomatosis is a rare disease, characterized by necrotizing granulomatous inflammation of important organ of the body. This inflammation damages important organ of the body by limiting blood flow to those organs and destroy normal tissue. Although the disease can involve any organ system, Wegener's granulomatosis mainly affects the upper and lower respiratory tract, kidneys. Skin, Eye, Musculoskeletal system and nervous system may also be affected. The prevalence of the disease is 3 persons per 1,00,000/- equally in both sexes. The German pathologist Friedrich Wegener first described the disease in 1936. In 1954, Godman and Churg more fully described the disease. They established three main clinical criteria of WG (Vasculitis, glomerulonephritis, respiratory tract involvement). The manifestation of this disease and organ involvement may vary widely. We report an unusual case of WG in which the patient presented with multiorgan involvement (Nervous system, Respiratory tract, Skin, Eye, Liver, Kidney) and most acute presentation of them is diffuse alveolar hemorrhage. J. Dhaka National Med. Coll. Hos. 2016; 22 (02): 47-50